2018
DOI: 10.1111/hdi.12652
|View full text |Cite
|
Sign up to set email alerts
|

The prevention of hepatitis C virus transmission to hemodialysis patients and staff members

Abstract: In this review article, we cover 4 topics very relevant to those involved in the care of hemodialysis (HD) patients and in the management of a HD unit. We start with an overview of the progress made over the last 25 years to reduce hepatitis C virus (HCV) transmission in HD. Next, we discuss the potential strategies to prevent the residual ongoing transmission of HCV to HD patients. Third, we discuss the actions to be taken if a seroconversion for HCV is nevertheless detected in a HD patient. Finally, we brief… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…Finally, there are concerns regarding dialysis‐related transmission of HCV. Despite awareness and universal infection control precautions nosocomial transmission still occurs in dialysis units . A short‐to medium term goal should be HCV‐free dialysis units to minimize the risk of new HCV cases occurring in hemodialysis patients.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, there are concerns regarding dialysis‐related transmission of HCV. Despite awareness and universal infection control precautions nosocomial transmission still occurs in dialysis units . A short‐to medium term goal should be HCV‐free dialysis units to minimize the risk of new HCV cases occurring in hemodialysis patients.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, HCV prevalence remains far higher in people receiving hemodialysis than in the general population. [48][49][50] In low-income countries, both transfusion of contaminated blood products and hand-borne nosocomial transmission continue to be major infection pathways, 13 but for high-income countries, the latter is currently the key pathway. 51 Interferon-based therapies are not well tolerated by hemodialysis patients, as reflected in treatment rates of 1 to 4% in high-income countries.…”
Section: Hemodialysis Recipientsmentioning
confidence: 99%
“…51 Thorough training and strict adherence to infection control protocols by staff are necessary to prevent future infections. 48,58 There also is a need for rigorous screening to ensure that no new recipients of hemodialysis have HCV since such cases would allow for the reintroduction of HCV in hemodialysis units where progress has been made toward HCV elimination. The widespread treatment of HCV in people receiving hemodialysis will likely achieve the "treatment as prevention" outcome of reducing the incidence of transmission in hemodialysis units when paired with appropriate prevention measures.…”
Section: Hemodialysis Recipientsmentioning
confidence: 99%
“…Infection control procedures employed for other blood‐borne pathogens such as HBV and HIV also prevent the nosocomial transmission of HCV. KDIGO recommends full compliance with these practices (Recommendation 3.1; see Box 3) which include staff education, hand hygiene before and after patient contact, glove use for patient contact, and use of single‐use vials for parenteral medicines . Dialysis stations should be cleaned thoroughly with low‐level disinfectant following dialysis treatment and with higher‐level disinfectants when visible contamination is present.…”
Section: Kdigo Guideline Recommendationsmentioning
confidence: 99%
“…Studies of HCV outbreaks in HD units consistently have demonstrated incomplete adherence to these practices with infection control audits revealing breakdowns in hand hygiene and in handling of parenteral medications as well inadequate cleaning of dialysis stations . KDIGO and the CDC recommend regular audits of infection control practices within HD units (Recommendation 3.1.1) …”
Section: Kdigo Guideline Recommendationsmentioning
confidence: 99%